2016
DOI: 10.1016/j.socscimed.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Does integration of HIV and sexual and reproductive health services improve technical efficiency in Kenya and Swaziland? An application of a two-stage semi parametric approach incorporating quality measures

Abstract: Theoretically, integration of vertically organized services is seen as an important approach to improving the efficiency of health service delivery. However, there is a dearth of evidence on the effect of integration on the technical efficiency of health service delivery. Furthermore, where technical efficiency has been assessed, there have been few attempts to incorporate quality measures within efficiency measurement models particularly in sub-Saharan African settings.This paper investigates the technical ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 34 publications
2
35
1
6
Order By: Relevance
“…DEA models include input-and output-oriented models. An input-oriented model reflects the degree to which a DMU can reduce its input without changing its outputs, while an output-oriented model indicates the degree to which a DMU can expand its output without changing its inputs [24]. In this study, the outputs are associated with the quantity of maternal and child health services.…”
Section: Dea Modelmentioning
confidence: 99%
“…DEA models include input-and output-oriented models. An input-oriented model reflects the degree to which a DMU can reduce its input without changing its outputs, while an output-oriented model indicates the degree to which a DMU can expand its output without changing its inputs [24]. In this study, the outputs are associated with the quantity of maternal and child health services.…”
Section: Dea Modelmentioning
confidence: 99%
“…Moreover, facility type was also found to be an useful predictor of hospital e ciency whereby facilities operating at a large scale may realize greater technical e ciency due to increasing returns to scale. [30] Third, a higher mortality rate (low quality health services) was found to raise the costs of the hospitals [34] and thereby to erode hospital e ciency. Fourth, shorter average lengths of stay was expected to improve the use of medical beds and enhance e ciency.…”
Section: Study Variablesmentioning
confidence: 99%
“…[25][26][27][28][29] However, weak and, on occasions, negative impacts of IC on hospital e ciency were also found. [30][31] As such, there is an opportunity to add to the literature by directly assessing the impact of IC on hospital e ciency.…”
mentioning
confidence: 99%
“…The Integra Initiative, which assessed the impact of different models of delivering integrated HIV-SRH service delivery in 40 health facilities in Kenya and Swaziland on service and health outcomes, found mixed effects in terms of technical efficiency of service delivery [40, 41]. Number of HIV and STI services in maternal and child health units, public ownership, and facility type resulted in positive effects on technical efficiency of service delivery, but number of HIV services in the same clinical room, relative number of clinical staff to overall staff, proportion of HIV services provided in facility, and rural location had negative effects on technical efficiency of integrated HIV-SRH services [41].…”
Section: Introductionmentioning
confidence: 99%
“…Number of HIV and STI services in maternal and child health units, public ownership, and facility type resulted in positive effects on technical efficiency of service delivery, but number of HIV services in the same clinical room, relative number of clinical staff to overall staff, proportion of HIV services provided in facility, and rural location had negative effects on technical efficiency of integrated HIV-SRH services [41]. Another analysis of these data that quantified the extent and type of integration between HIV and SRH services in Kenya and Swaziland suggested that both structural integration (infrastructure and multi-tasking providers in same facility) and functional integration (delivery of care to clients in one place at one time) are needed for effective integration of these services to clients [34].…”
Section: Introductionmentioning
confidence: 99%